ANALISIS PERANAN AUDIT FORENSIK TERHADAP KASUS PT. DUTA PALMA GROUP - Daharo, Muhammad Irvan Ayang; Br Bangun, Riskana Natalia; Br Subakti, Rifka Sari; Dwilita, Handriyani (Accounting and Business Journal, 2024)
This study explores the role of forensic audits in identifying alleged fraudulent acts in PT. Duta Palma Group, a large company in the agribusiness sector in Indonesia. This case involves legal irregularities related to land management, finance, and authority that cause significant state losses, including ecological impacts. The study uses a qualitative approach based on document analysis from official investigation and audit reports. The findings show that forensic audits are effective in uncovering manipulation of financial statements, tracking suspicious fund flows, and uncovering money laundering through cross-border shell company structures. State losses, which include economic and environmental aspects, are estimated to reach hundreds of trillions of rupiah. This study emphasizes the importance of forensic audits as an instrument to encourage accountability and transparency, especially in the agribusiness sector. Prevention efforts require strengthening internal supervision, developing the capacity of auditors, and strict law enforcement.